Modulation of VEGF-induced endothelial cell cycle protein expression through cyclic AMP hydrolysis by PDE2 and PDE4 - Favot, Laure; Keravis, Thérèse; Lugnier, Claire (Thrombosis and Haemostasis, 2004)
Endothelial cell proliferation in response to VEGF plays an important role in physiological and pathological angiogenesis. The role of PDE2 and PDE4 in VEGF-induced proliferation in HUVEC was investigated: 1) VEGF increased cAMP-hydrolytic activity by up-regulating the expression of PDE2 and PDE4 isozymes; 2) VEGF increased progression in cell cycle with an increase in p42/p44 MAP kinase, cyclin A and cyclin D1 expressions and with a decrease in p21waf1/cip1 and p27kip1 expressions; 3) EHNA (20 µM), a selective PDE2 inhibitor, RP73401 (10 µM), a selective PDE4 inhibitor blocked the VEGF-induced increase in p42/p44 MAP kinase expression; 4) RP73401, but not EHNA, blocked the VEGF-induced increase in cyclin A and decrease in p27kip1 expressions; 5) EHNA, contrary to RP73401, enhanced the VEGF-induced increase of cyclin A and decrease of p27kip1. EHNA and RP73401 together blocked the VEGF-induced increase in cyclin D1 and decrease in p21waf1/cip1 expressions; Inhibition of VEGF-upregulated PDE2 and PDE4 reversed the VEGF-induced alterations in cell cycle protein expression, bringing back endothelial cells to a non-proliferating status. Consequently, PDE2 and PDE4 inhibitions were able to inhibit VEGF-induced endothelial cell proliferation by restoring cell cycle key protein expression, and might thus be useful in excessive angiogenesis. Furthermore, the differences between PDE2 and PDE4 effects may suggest compartmentalized effects.
Keywords: Angiogenesis and inhibitors; endothelial cells; gene expression; signal transduction; protein function / activity